2001
DOI: 10.1515/bc.2001.163
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Evolution of (??)8-Barrel Enzymes

Abstract: The (?[alpha)8-barrel is the most versatile and most frequently encountered fold among enzymes. It is an interesting question how the contemporary (?[alpha)8-barrels are evolutionarily related and by which mechanisms they evolved from more simple precursors. Comprehensive comparisons of amino acid sequences and threedimensional structures suggest that a large fraction of the known (?[alpha)8-barrels have divergently evolved from a common ancestor. The mutational interconversion of enzymatic activities of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 29 publications
3
59
0
Order By: Relevance
“…It has been postulated that HisA and HisF evolved from a common (␤␣) 4 -halfbarrel by a series of gene duplication and diversification events (4,11). In the present work, the first steps of this hypothetical evolutionary pathway were reconstructed experimentally, by using HisF-C as a model for the ancestral half-barrel (Fig.…”
Section: Production Of Chimeric (␤␣)8-barrels By the Crosswise Fusionmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been postulated that HisA and HisF evolved from a common (␤␣) 4 -halfbarrel by a series of gene duplication and diversification events (4,11). In the present work, the first steps of this hypothetical evolutionary pathway were reconstructed experimentally, by using HisF-C as a model for the ancestral half-barrel (Fig.…”
Section: Production Of Chimeric (␤␣)8-barrels By the Crosswise Fusionmentioning
confidence: 93%
“…It appears that both HisF and HisA are composed of two structural domains, namely the corresponding N-and C-terminal half-barrels. These results suggest an evolutionary scenario according to which a primordial gene encoding a (␤␣) 4 -half-barrel as a subunit of a homodimeric enzyme was duplicated and fused to yield a monomeric, ancestral (␤␣) 8 -barrel, from which HisF, HisA, and presumably also TrpF evolved by a series of further gene duplication and diversification events (4,11). Moreover, it was postulated that (␤␣) 4 -halfbarrels are independently evolving domains, implying that new (␤␣) 8 -barrels could be generated by mixing and joining (␤␣) 4 half-barrels from an existing pool (18).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The importance of the electrostatic properties of this fold has also been discussed [65,66]. Evolutionary studies [22,25,67] have shown that the TIM-barrel has possibly evolved from two half barrels [68]. Also, recent enzyme design studies [69,70], using either directed evolution [71] or computational approaches [72], highlight the importance of the TIM-barrel fold as an important framework for making non-natural enzymes.…”
Section: The Tim-barrel Foldmentioning
confidence: 99%
“…A scaffold that has caught a lot of attention is the (ba) 8 barrel fold (also known as TIM-barrel). About 10% of all the enzymes with known structure adopt this fold.…”
Section: Introductionmentioning
confidence: 99%